Feasibility and Preliminary Efficacy of an Online Intervention to Increase Physical Activity in Nova Scotian Cancer Survivors: A Randomized Controlled Trial - Forbes, Cynthia C (JMIR Cancer, 2015)
BACKGROUND: Physical activity (PA) behavior change interventions among cancer survivors have used face-to-face, telephone, email, and print-based methods. However, computer-tailored, Internet-delivered programs may be a more viable option to achieve PA behavior change. OBJECTIVE: The objective of this study is to test the feasibility and preliminary efficacy of a Web-based PA behavior change program among cancer survivors. METHODS: Nova Scotian cancer survivors (N=415) who previously expressed interest in a research study were approached. Interested participants were asked to complete an online assessment of PA and quality of life (QOL) before being randomized to either a theory-based PA behavior change program using the PA tracking website UWALK (UCAN; n=48) or usual care (UC; n=47). After the intervention (9 weeks), participants completed another online assessment of PA and QOL as well as measures to evaluate the program and website. Descriptive analyses from surveys and Web analytic software were used to assess feasibility and mean change scores were used to test efficacy. RESULTS: Of all contacted survivors, 95 (22.3%, 95/415) completed baseline measures and were randomized with 84 (88%, 84/95) completing the 9-week assessment. The behavior change program and website were rated highly on the satisfaction items. Average logins were 10.3 (1.1 per week) and 26.0% (111/432) of the weekly modules were completed. Most participants (71%, 29/41) indicated they were more aware of their daily PA levels and 68% (28/41) found the site easily navigable. Adjusted group differences in total exercise minutes favored the UCAN group by an increase of 42 minutes (95% CI -65 to 150; P=.44, d=0.17). Results were more pronounced, though still nonsignificant, among those not meeting guidelines at baseline where UCAN increased PA by 52 minutes compared to a decrease of 15 minutes in UC (adjusted between group difference=75, 95% CI -95 to 244; P=.38, d=0.27). CONCLUSIONS: We found that Internet-delivery may be a feasible alternative to more costly methods to promote PA among Nova Scotian cancer survivors. Moreover, there was a trend toward increased PA among those in the UCAN group, especially among those who were not meeting PA guidelines at baseline. Future research should focus on recruiting inactive cancer survivors and engaging them in the website to determine the optimal potential of Web-based interventions for promoting PA in cancer survivors.